Controlled Growth of Indium Selenides by High-Pressure and High-Temperature Method - Dai, Yajie; Zhao, Shouxin; Han, Hui; Yan, Yafei; Liu, Wenhui; Zhu, Hua; Li, Liang; Tang, Xi; Li, Yang; Li, Hui; Zhang, Changjin (Frontiers in Materials, 2022)
Controlled growth of indium selenides has attracted considerable research interests in condensed matter physics and materials science yet remains a challenge due to the complexity of the indium-selenium phase diagram. Here, we demonstrate the successful growth of indium selenides in a controllable manner using high pressure and high temperature growth technique. The γ-InSe and α-In2Se3 crystals with completely different stoichiometry and stacking manner of atomic layers have been controlled grown by subtle tuning growth temperature, duration time and growth pressure. The as-grown γ-InSe crystal features a semiconducting property with a prominent photoluminescence peak of ∼1.23 eV, while the α-In2Se3 crystal is ferroelectric. Our findings could lead to a surge of interest in the development of controlled growth of high-quality van der Waal crystals using high pressure and high temperature growth technique and will open perspectives for further investigation of fascinating properties and potential practical application of van der Waal crystals.